Prevalence and correlates of common mental disorders among dental students in Brazil - Graner, Karen Mendes [UNESP]; Alves de Moraes, Antonio Bento; Torres, Albina Rodrigues [UNESP]; Pereira Lima, Maria Cristina [UNESP]; Rolim, Gustavo Sattolo; Abreu Ramos-Cerqueira, Ana Teresa de [UNESP] (Public Library Science, 2018)
This study aimed to estimate prevalence of common mental disorders (CMD) and associated factors among dental students. In this cross-sectional study, 230 students answered a questionnaire and instruments to assess CMD (Self Reporting Questionnaire-20), hazardous alcohol consumption (Alcohol Use Disorder Identification Test), social support (Social Support Scale), perceptions of academic life (Dundee Ready Education Environment Measure), coping (Ways of Coping Inventory) and resilience (Resilience Scale). Bivariate analysis was conducted using the Chi-Square and Mann-Whitney tests. Logistic regression included all explanatory variables with p<0.20 in the bivariate analysis, besides sex and academic year. The explanatory variables were analyzed in five successive blocks (backward-stepwise), until all variables presented statistical significance in the final model (p<0.05). The prevalence of CMD was 45.2% (95%CI: 38.7-51.6), with no significant differences between sexes. Students with no extracurricular activities, who had negatively self-assessed their health status and their academic performance, were about four times more likely to present CMD, followed by receiving psychological or psychiatric treatment during university (AOR: 2.65; 95%CI: 1.1-6.1) and those with high scores for confrontive coping (AOR: 1.20; 95%CI: 1.0-1.4). Resilience was a protective factor for CMD among dental students (AOR: 0.93; 95%CI: 0.9-1.0). Aspects related to academic performance, health status and confrontive coping strategies were risk factors to students' mental health. Individuals with high levels of resilience showed lower prevalence of CMD. Further prospective studies could contribute to understanding the role of resilience among this population.